Fabrication of a phototheranostic nanoplatform for single laser-triggered NIR-II fluorescence imaging-guided photothermal/chemo/antiangiogenic combination therapy. (1st October 2022) - Lu, Feng; Sang, Ruoyu; Tang, Yu; Xia, Hui; Liu, Jiawei; Huang, Wei; Fan, Quli; Wang, Qi
Abstract: Phototheranostics that integrates real-time optical imaging and light-controlled therapy has recently emerged as a promising paradigm for cancer theranostics. Herein, a new small molecule dye DPP-BT-TPA with strong emission above 1000 nm and a redox-responsive prodrug camptothecin-combretastatin A4 (CPT-CA4) were designed and successfully synthesized. A multifunctional phototheranostic nanoplatform was then fabricated by encapsulating them within an amphiphilic polymer. The presence of DPP-BT-TPA enabled high-resolution imaging in the second near-infrared window (NIR-II) and efficient photothermal therapy. The prodrug was cleaved by the overexpressed glutathione (GSH) in the tumor microenvironment to release the chemotherapeutic drug CPT and the angiogenesis inhibitor CA4. Because this process can be accelerated with elevated temperature, laser-induced hyperthermia was utilized to control the drug release and enhance the therapeutic effect. Tumors in living mice were observed through NIR-II imaging after intravenous injection of the obtained nanoparticles. Improved antitumor efficacy by photothermal/chemo/antiangiogenic combination therapy was achieved with a NIR laser both in vitro and in vivo. This work provides a promising strategy for developing tumor microenvironment responsive and light-controlled theranostic platforms. Statement of significance: Fluorescence imaging in the second near-infrared (NIR-II, 1000–1700 nm) window and near-infrared light-controlled drug release have been recognized as efficient strategies for cancer theranostics. Herein, we present a phototheranostic platform fabricated with a biocompatible NIR-II emissive dye DPP-BT-TPA and a redox-responsive prodrug camptothecin-combretastatin A4 (CPT-CA4). DPP-BT-TPA not only provides high-resolution NIR-II imaging in vivo but also enables efficient photothermal therapy. In addition, the photothermal effect largely accelerates the release of the chemotherapeutic drug CPT and the angiogenesis inhibitor CA4 in the glutathione-overexpressed tumor microenvironment. Thus, the designed phototheranostic platform can be used for NIR-II imaging-guided photothermal/chemo/antiangiogenic combination therapy for tumors with a single laser. Graphical abstract: Image, graphical abstract